Current Challenges in Revenue Mobilization : Improving Tax Compliance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This paper addresses core challenges that all tax administrations face in dealing with noncompliance-which are now receiving renewed attention. Long a priority in developing countries, assuring strong compliance has acquired greater priority in countries facing intensified revenue needs, and is critical for fairness and statebuilding. Series: Policy Papers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet